Abiraterone Rechallenge Based on Sequential Testing of Androgen Receptor Splice Variant 7 Expression in Circulating Tumor Cells: A Case Report - Nagaya, Naoya; Kanayama, Mayuko; Nagata, Masayoshi; Horie, Shigeo (Frontiers in Oncology, 2020)
Serial analysis of circulating tumor cells such as androgen receptor splice variant 7 is useful in selecting treatments for castration-resistant prostate cancer. We report a case who had been positive for androgen receptor splice variant 7 in circulating tumor cells before docetaxel, and was subsequently treated with abiraterone rechallenge because of the negative conversion of androgen receptor splice variant 7 following docetaxel. Although the rechallenge of anti-androgen agent based on circulating tumor cells analysis is expected to be an effective approach, it is yet to be reported. Thus, we chose the candidate for abiraterone rechallenge based on serial circulating tumor cells analyses by the AdnaTest. As a result, the patient responded to abiraterone that he once had developed resistance to. Our findings reinforce the utility of AR-V7 as a biomarker in the setting of post-chemo androgen-targeted-therapy rechallenge.